Awareness, practices and perspectives on ensuring access to ideally packaged iodized salt in Nigeria - Oluwaseun Ariyo; Opeyemi Akintimehin; Anuoluwapo Funmilayo Taiwo; Thelma Nwandu; Bukola Olanrewaju Olaniyi (Elsevier, 2023)
Salt iodization is a positive exemplar of a sustainable public-private partnership in promoting better nutrition outcomes in many countries. However, the gains in the past decades are gradually being eroded, following laxity in policy implementation, monitoring and regulatory roles resulting in increasing access to non-labelled salt in the Nigerian market. This study was designed to evaluate the awareness, practices and perspectives on salt iodization and regulations among salt marketers and consumers in Ibadan, Oyo state.This mixed-method study was carried out in seven major markets across Ibadan metropolis. A three-stage sampling technique was used to select 77 salt users/clients, 103 salt vendors, 12 salt wholesalers and four regulators/producers. Interviewer-administered questionnaire was used to collect information on types/brands of salt, handling, retail practices, awareness, and salt purchase preference. Structured in-depth interview was used to elicit information on existing regulations, compliance level, and monitoring activities. Descriptive statistics were used to analyse quantitative data. Interviews were tape-recorded, transcribed verbatim and analyzed thematically.Males constituted 66.7%, 1.0% and 14.3% of respondents among wholesalers, retail vendors, and clients, respectively, with 100.0%, 58.3% and 84.4% having at least primary education. All wholesalers and 30.1% of retail vendors used shaded structure. About 67% of the wholesalers and 58.3% of the retailers sold branded salt. Clients' basis for the use of non-branded salt included cheapness and greater quantity (54.5%), higher intensiveness/saltiness and greater quantity (22.1%), and cheaper cost (18.2%). Only 3% of the consumers were aware of mandatory salt iodization, 3.9% were aware of guidelines on salt marketing and only 18.2% handled salt safely. Safe handling practices were found among all wholesalers and 44.7% of the retailers. Qualitative findings revealed the existence of regulation on the production, packing and marketing of salts in Nigeria, however, enforcement and monitoring at the market level is weak.The demand and use of industrial salt in food preparation remain widespread among consumers in Ibadan, Nigeria following limited awareness of salt iodization programme and its benefits. Regulations on salt marketing should be enforced at all levels and nutrition education on salt iodization should be intensified.